Gestão pública: busca da igualdade social a partir da ação afirmativa cota no ensino superior brasileiro - Arrigoni, Fernando José (2018)
The research objective was to verify if the academic performance difference between Quota holders and non-Quota holders in the ‘Exame Nacional do Ensino Médio’ (ENEM - National High School Examination) (before the student enters higher education) is reduced in relation to that calculated in the Academic Income Coefficient (CRA) ( after the student joins/attends higher education) and if this reduction is also reflected in the graduate’s life. The quantitative survey was carried out with 9,700 graduates from Quotas and non-Quota holders who completed their respective courses in the period 2012/1 to 2017/1 and who joined after UFES (Universidade Federal do Espirito Santo) adopted the quota system (2008). It was found that the academic performance of the Quotients in the ENEM was lower than that of the Quotients, and that in the CRA, 64.91% of the subvariables indicated that there was no difference in performance between the two groups. Using the Analysis of Feeling, qualitative research verified that the fact that the student enrolled in higher education and having completed it led to changes in his life that made him feel socially more equal to non-Quota holders. The speeches expressing the feelings of the interviewees were polarized into positive and negative. Those that did not have this characterization were disregarded. One hundred percent of the polarized lines of the graduates interviewed indicate that there have been very large positive changes in their lives (citizenship) and 81.80% indicate that there have been positive changes in their relationship with the labor market. Both the academic performance and the speeches of the interviewees point to the consequences of the Quotations, the feeling of social approximation of the Quota holders in relation to the non-Quota holders. Twenty-one Quota holders were interviewed. As in the interviews, the Quota holders mentioned administrative issues related to leveling and resources for their maintenance in the courses, and 10 leaders were also interviewed. Thus, 60.00% of the polarized statements of the Quota holders and 55.60% of the managers characterize the leveling actions as negative. Regarding the attendance actions, aiming to stay in the course, 50.00% of the statements of the Quotients and 62.50% of those of the leaders characterize them as positive.